The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1111/j.1439-0310.2006.01306.x
|View full text |Cite
|
Sign up to set email alerts
|

Observational Evidences of Vocal Learning in Southern Elephant Seals: a Longitudinal Study

Abstract: Vocal learning in mammals is sparsely documented, and there are few reports of vocal learning by wild mammals. In particular, no information based on longitudinal data for identified individuals exists, even for well‐studied highly social species in which vocal communication is an important aspect of social life. We present such information for the southern elephant seal (Mirounga leonina). We studied a small breeding population in the Falkland Islands over 8 yr (1995–2002). We recorded approx. 2400 agonistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 47 publications
0
51
0
2
Order By: Relevance
“…The latter has found in three distantly related groups of mammals (humans, bats, and cetaceans) and three distantly related groups of birds (parrots, hummingbirds, and songbirds) (Nottebohm 1972;Janik and Slater 1997). Recent studies have also discovered evidence for vocal learning in seals (Sanvito et al 2007) and elephants (Poole et al 2005). However, it is only in humans and the three vocal learning bird groups that the brain pathways for learned vocalization have been studied.…”
Section: Vocal Learningmentioning
confidence: 99%
“…The latter has found in three distantly related groups of mammals (humans, bats, and cetaceans) and three distantly related groups of birds (parrots, hummingbirds, and songbirds) (Nottebohm 1972;Janik and Slater 1997). Recent studies have also discovered evidence for vocal learning in seals (Sanvito et al 2007) and elephants (Poole et al 2005). However, it is only in humans and the three vocal learning bird groups that the brain pathways for learned vocalization have been studied.…”
Section: Vocal Learningmentioning
confidence: 99%
“…Sanvito et al (2007) show how more detailed longitudinal data on vocal development in elephant seals provides much stronger data on production learning than does study of dialects. Sanvito et al (2007) recorded 29 male elephant seals throughout vocal development. The observed changes in vocalizations observed are well explained by vocal learning, with young peripheral males imitating vocalizations produced by established successful males.…”
Section: Geographical and Temporal Variation In Callsmentioning
confidence: 99%
“…Vocal convergence is well known in humans and is one aspect of a phenomenon called vocal accommodation (Street and Giles 1982 ;Giles 1984). Sanvito et al (2007) showed on the breeding ground of southern elephant seals (Mirounga leonina) that agonistic calls of subordinate males tended to converge on those of the local dominant male.…”
Section: Vocal Convergence As Animals Form a Groupmentioning
confidence: 99%